Assessing the Role of Adaptive Materials in Inclusive Classrooms at Colon Integrated School - Largo, Ma. Isabel; Pinili, Lilibeth; Mangubat, Randy; Calasang, Veronica; Cabigon, Ann Frances; Espina, Raymond (International Journal of Educational Studies, 2025)
This study explored the level of access to inclusive education resources among teachers and its relationship to learners’ academic performance. It focused on three key resources: adaptive materials, assistive technology, and classroom aides. Descriptive method of research was utilized, using frequency and percentage for the relevant information of teachers, while, mean for the level of access to resources and correlation analysis for the test of relationship. Data showed that teachers had positive access to these resources, with adaptive materials rated as effective and relevant, assistive technology seen as enhancing student independence, and classroom aides viewed as collaborative and supportive. However, despite these positive evaluations, no significant relationship was found between the level of access to these resources and learners’ academic performance, suggesting that other factors may play a role in influencing outcomes. The study also highlighted areas for improvement, such as the need for enhanced teacher training, better integration of resources into the curriculum, and improved technical support and maintenance for assistive technology. Based on these findings, the study recommends a strategic plan to address these gaps, focusing on teacher training, resource integration, collaboration among staff, and holistic support for learners. The plan aims to maximize the impact of inclusive education resources, ensuring that they contribute more effectively to both academic and non-academic outcomes. This study underscores the importance of a comprehensive approach to inclusive education, where resources are not only accessible but also strategically utilized to meet the diverse needs of learners. The findings provide valuable insights for educators, policymakers, and stakeholders working towards inclusive and equitable education for all.